Gambaran Tingkat Stres dan Pemberian Psikoedukasi Coping Stres Sederhana pada Ibu Rumah Tangga di Dusun Jurit Melalui Posyandu Mental - Dalia Ilmiah, Movi; Ramadhani, Habib (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to determine the level of stress among housewives in Jurit Hamlet and to provide psychoeducation on simple stress coping strategies through the Mental Posyandu program. A quantitative descriptive approach was used. Data collection was conducted using the Depression Anxiety Stress Scale (DASS-42) questionnaire, which focused on the stress dimension, with a sample size of 40 housewives. The results showed that the majority of respondents fell into the normal stress category (90%), while 7.5% were in the mild category and 2.5% in the moderate category. Based on these results, the psychoeducational intervention focused on respondents with moderate stress levels, covering stress awareness, sources of stress, and coping techniques such as deep breathing relaxation, time management, and utilizing social support. Evaluation was conducted through direct observation and participant feedback following the activity. The results of the activity indicated an increase in participants’ understanding of stress and its management strategies, as well as a decrease in subjective stress levels Participants also demonstrated active engagement in sharing experiences and strategies for dealing with daily pressures. However, this activity has limitations, including a relatively small number of respondents, the absence of a control group, and an evaluation that remains short-term and subjective, thus unable to fully describe the intervention’s long-term effectiveness. The implications of this activity suggest that simple stress coping psychoeducation through the Mental Health Posyandu has the potential to be an effective promotive and preventive measure in improving the mental health of homemakers at the community level. Therefore, the sustainable, structured, and community-needs-based development of the Mental Health Posyandu program is crucial for strengthening family psychological resilience and preventing mental health issues in the broader community.